Oxford classification of IgA nephropathy and C4d deposition; correlation and its implication - Ashutosh Rath; Rohit Tewari; Satish Mendonca; Sonia Badwal; Vijay Shrawan Nijhawan (Journal of Nephropharmacology, 2016)
Introduction: IgA nephropathy (IgAN) is well known to be the most common form of primary glomerulonephritis throughout the world. The histopathological changes are wide and varied as brought out by the various classification systems like the Haas and Oxford systems. C4d is a well-known biomarker of the complement cascade and has recently been implicated in certain native renal diseases. We attempted to characterize C4d deposition in IgAN and correlate this with histopathology by the Oxford classification system. Patients and Methods: This retrospective study included renal biopsies of 15 cases of IgAN diagnosed on histopathology and immunofluorescence over a period of 2 years. Demographic parameters of age and sex were reviewed. The Oxford classification system was applied to score the cases and immunohistochemistry for C4d was done on all cases to characterize staining pattern and intensity and was correlated with Oxford classification. Results: On histological examination, the cases showed various combinations of lesions ranging from M0E0S0T0 to M1E1S1T1. C4d deposition was found to be occurring mainly in mesangial location (12/15 cases, 80%). Forty percent cases showed C4d deposition in the glomerular capillary walls in a segmental fashion and 26.67% showed global pattern. Other patterns of deposition were arteriolar (53.33%), in peritubular capillaries (26.67%) and in tubular epithelium (20%). Conclusion: On comparing the various patterns of deposition of C4d with the four variables of the Oxford classification system, we found that segmental and global deposition of C4d correlated best with endocapillary proliferation.